2019
DOI: 10.21831/jptk.v25i1.23328
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothetic Model of Integrated Production-Based Learning with the 21st Century Learning Skills in Mechanical Engineering

Abstract: Vocational education building and development must consider the needs of the industry and the demands of 21st-century skills graduates. For these two requirements, it is necessary to innovate the learning model to improve the students’ learning experience and graduates’ performance. This study aims to develop a production-based learning model that is integrated with 21st-century learning skills to improve skills in mechanical engineering. The study employed focus group discussion and experts’ judgment. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Meanwhile, in the standard learning process, it has been determined that learning in Vocational High School must emphasize the implementation of discovery/inquiry, problem-based, and project-based learning models depending on the characteristics of each subject and program of expertise. In vocational education emphasizing the integration of various disciplines and practical abilities based on industry needs, project-based learning (PjBL) is the most appropriate model (Yudiono et al, 2019). Various studies have shown that PjBL can improve the quality of vocational education (Sukamta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in the standard learning process, it has been determined that learning in Vocational High School must emphasize the implementation of discovery/inquiry, problem-based, and project-based learning models depending on the characteristics of each subject and program of expertise. In vocational education emphasizing the integration of various disciplines and practical abilities based on industry needs, project-based learning (PjBL) is the most appropriate model (Yudiono et al, 2019). Various studies have shown that PjBL can improve the quality of vocational education (Sukamta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Soft skills development becomes the priority for the development of learning models and the skills needed by industry. Communication skills, collaboration, creativity, and critical thinking integrated in production based learning can improve student's soft and hard skills (Yudiono, et al 2019). The competency needs are not only significant resource management and mechanical knowledge strengthening, but also developing the competency requirements needed by the industry.…”
Section: Discussionmentioning
confidence: 99%
“…The production-based learning steps that need to be adopted by the instructors to facilitate their students' learning actively, interactively, and practically. Such an active learning process contributes, as Yudiono et al (2019) argue, integration of efficacy, feasibility, propriety, and accuracy in school production unit steps meet the expected criteria of 21st century learning skills.…”
Section: Work-based Active Learningmentioning
confidence: 98%
“…According to Chukwu and Omeje (2017), school-based production units are connected with expert professional courses and it is a best platform for alternative of students' industrial work experience. Students receive performance and learning experience through school production by focusing areas of expertise, collaboration, critical thinking, and communicating (Yudiono et al, 2019). Work experience in school production unit enhances the production skills needed in industry and other work situations with sufficient exposure to theory and practice.…”
Section: Work-based Experiential Learningmentioning
confidence: 99%